Analysis of the Utilization Level of Port Facilities at Belawan Samudera Port - Manurung, Ester; Firmansyah, Firmansyah; Wulandari, Wulandari; H, Afriani; hariski, M; Roiska, Riris (Program Pascasarjana Universitas Sriwijaya, 2025)
Belawan Ocean Fishing Port (PPS) is one of the largest fishing ports in North Sumatra. PPS Belawan aims to increase the income of fishing communities through the provision of fishing port facilities and infrastructure. The study aims to analyze the optimization of the level of utilization of basic, functional and supporting facilities at the Belawan Ocean Fishing Port and to determine the condition of these facilities. The latest conditions in the field through field surveys show that there are several facilities whose utilization levels are not optimal and whose conditions are not good, such as the port pool. The study was conducted at PPS Belawan, North Sumatra from December 15, 2024 to January 15, 2025. The method used in this study is the survey method. The data collected in the study are primary data in the form of interviews with several sources whose daily activities are related to port facilities, namely basic facilities, functional facilities, and supporting facilities. The data analysis used is descriptive which explains the condition of the port facilities and the level of utilization of port facilities from several facilities which can be calculated systematically. The results of the research show that the Belawan ocean fishing port facilities whose level of utilization can be calculated are still not optimal, even far from optimal, while the conditions of all the facilities required to be in ocean fishing ports, namely those divided into basic facilities, functional facilities and supporting facilities are in quite good condition, and can support port operations quite well.